2x^2 + 14x + 12 = 0
x^2 + 7x + 6 = 0
( x + 1 )( x + 6 ) = 0 ==》 x = - 1 Or x = - 6
You will add them all together, then multiply the sum by 6.
713/6 = 118.833333
this rounded to the nearest hundredth
$118.83 per month
Answer: 49
Step-by-step explanation:
a=1 ,b=14, c=?
b^2-4ac =0
(14)^2-4(1)(c)=0
196-4c=0
196=4c
c=49
Check:
(x)^2+2(x)(7)+(7)^2
x^2+14x+49
(x+7)^2
Answer: 4x+36
Step-by-step explanation:
1- 4 times x=4x
2- 4 times 9=36
3- so it is 4x+36
The equation of the line will be y = 2x - 2.
<h3>What is an equation of the line?</h3>
A linear equation with a degree of one is referred to as a line equation. Two variables, x, and y are present in the equation of the line. The third parameter is the line's slope, which indicates the line's elevation.
The general form of the equation of the line is given as:-
y = mx + c
Given that the equation of the line is passing through the point ( -2,0) and the slope of the line is 2.
The equation of the line will be calculated as:-
y = mx + c
-2 = 0 + c
c = -2
y = mx + c
y = 2x - 2
Therefore, the equation of the line will be y = 2x - 2.
To know more about an equation of the line follow
brainly.com/question/18831322
#SPJ1